Web-Based Library Information System Design : Study at Pasundan 7 Junior High School, Bandung - Asep Mulyana; Dani Rohpandi; Egi Badar Sambani; Miftah Fahmi; Nono Sudarsono; Mohammad Hamdani (LPPM STMIK Mardira Indonesia, 2023)
School libraries generally aim to provide information services on borrowing and returning books to students and teachers. The library of Pasundan 7 Bandung Junior High School has a large collection of books, both in the form of textbooks, collections of questions, magazines and newspapers. However, this library has not been well managed because all activities still use manual methods and do not have good documentation. This can be seen from the way students experience difficulties when looking for the desired book, then the process of recording borrowing and returning books that are still manual so that it takes a long time and the data storage is not guaranteed, the number of scattered records that confuse officers when matching data to make reports, because it is only stored in the form of ordinary archives that are easily lost. Therefore, a web-based library information system is needed at Pasundan 7 Bandung Junior High School. The Library Information System of SMP Pasundan 7 Bandung aims to assist library staff in minimizing service time with the help of computerized transactions, especially in book loan and return transactions. In designing an information system, all data related to the library is stored in a file warehouse called a database. To produce a good and correct database, it is necessary to carry out system design stages. The goal is to produce good data input. This Final Project discusses the design of creating a web-based information system, which can assist library staff in the process of delivering library information at Pasundan 7 Bandung Junior High School. This research focuses on designing a library information system in a school environment. The purpose of this research is to change the pattern of conventional services into computerization to facilitate data management in book borrowing and returning transactions in preventing data loss. The research method used is descriptive analysis method, which is a research method that tries to describe the object or subject under study objectively, and aims to describe the facts systematically and the characteristics of the object and the frequency studied precisely. Information system design is built using the waterfall method. Or through sequential stages in the hope of producing a design that is in accordance with the existing target needs. Data collection methods by means of interviews and direct observation. The results showed that using a computerized system is much more effective than the conventional way and even more efficient. The effectiveness of implementing a web-based Library Information System at Pasundan 7 Bandung Junior High School can be seen from the service process carried out.